The Arecibo Ultra-Deep Survey. Issue 3 (21st December 2020) - Xi, Hongwei; Staveley-Smith, Lister; For, Bi-Qing; Freudling, Wolfram; Zwaan, Martin; Hoppmann, Laura; Liang, Fu-Heng; Peng, Bo
ABSTRACT: The Arecibo Ultra-Deep Survey (AUDS) is a blind H i survey aimed at detecting galaxies beyond the local Universe in the 21-cm emission line of neutral hydrogen (H i ). The Arecibo L -band Feed Array (ALFA) was used to image an area of 1.35 deg 2 to a redshift depth of 0.16, using a total on-source integration time of over 700 h. The long integration time and small observation area makes it one of the most sensitive H i surveys, with a noise level of ∼75 μ Jy per 21.4 kHz (equivalent to 4.5 km s −1 at redshift z = 0). We detect 247 galaxies in the survey, more than doubling the number already detected in AUDS60. The mass range of detected galaxies is (M_H I [h_70^-2 M_]) = 6.32\!-\!10.76 . A modified maximum likelihood method is employed to construct an H i mass function (HIMF). The best fitting Schechter parameters are low-mass slope α = −1.37 ± 0.05, characteristic mass (M^* [h_70^-2 M_]) = 10.15 ± 0.09, and density Φ _* = (2.41 ± 0.57) × 10^-3 h_70^3 Mpc −3 dex −1 . The sample was divided into low- and high-redshift bins to investigate the evolution of the HIMF. No change in low-mass slope α was measured, but an increased characteristic mass M *, was noted in the higher redshift sample. Using Sloan Digital Sky Survey data to define relative galaxy number density, the dependence of the HIMF with environment was also investigated in the two AUDS regions. We find no significant variation in α or M *. In the surveyed region, we measured a cosmic H i density Ω _H I = (3.55 ± 0.30) × 10^-4 h_70^-1 . There appears to be no evolutionary trend in Ω _H I above 2σ significance between redshifts of 0 and 0.16.